2022
DOI: 10.1002/ffo2.145
|View full text |Cite
|
Sign up to set email alerts
|

The science behind “values”: Applying moral foundations theory to strategic foresight

Abstract: “Values” play an oversized role in strategic foresight: they help define scanning frameworks, direct scanning efforts, inform change driver and scenario development, and underpin change within various systems and domains (e.g., politics, society, etc.). And yet, values are largely understudied within foresight. They are rarely defined consistently or explored with reference to a theoretical model of how values emerge or evolve. Rather, values are researched using dissimilar methods depending on the foresight r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Recent literature exploring reasons for vaccine hesitancy among diverse groups has proposed that aligning pro-vaccination messages with the moral values and intuitions that people endorse may be more effective than vaccination mandates. Of note, a UK study (66) found that individuals who more strongly endorsed the moral foundation of liberty, which prizes freedom, choice, and individual rights (67), tended to be more vaccine hesitant. Members of the Collaboration on Social Science and Immunisation (Australia) also recently proposed that less coercive, trust-promoting measures should be prioritised over mandates, along with efforts to understand and address context-specific factors (68).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature exploring reasons for vaccine hesitancy among diverse groups has proposed that aligning pro-vaccination messages with the moral values and intuitions that people endorse may be more effective than vaccination mandates. Of note, a UK study (66) found that individuals who more strongly endorsed the moral foundation of liberty, which prizes freedom, choice, and individual rights (67), tended to be more vaccine hesitant. Members of the Collaboration on Social Science and Immunisation (Australia) also recently proposed that less coercive, trust-promoting measures should be prioritised over mandates, along with efforts to understand and address context-specific factors (68).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature exploring reasons for vaccine hesitancy among diverse groups has proposed that aligning pro-vaccination messages with the moral values and intuitions that people endorse may be more effective than vaccination mandates. Of note, a UK study [ 68 ] found that individuals who more strongly endorsed the moral foundation of liberty, which prizes freedom, choice, and individual rights [ 69 ], tended to be more vaccine hesitant. Members of the Collaboration on Social Science and Immunisation (Australia) also recently proposed that less coercive, trust-promoting measures should be prioritised over mandates, along with efforts to understand and address context-specific factors [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategic foresight can be thought of as the practical application of futures thinking through a distinct approach to research: it uses a host of tools and techniques to develop a rigorous appreciation of alternative and plausible futures (Cuhls, 2020; Mills & Wilner, 2023). Use of these tools falls across a spectrum of approaches, from foresight practitioners who follow a very prescribed, structured, and sequenced suite of methods and tools, to those who are relatively tools‐agnostic, responding to the needs, focus, and desired outcome of the research question that is being explored.…”
Section: What Is Strategic Foresight? a Drive‐by View For Beginnersmentioning
confidence: 99%